SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN MAHASISWA BARU JALUR BEASISWA DENGAN METODE TOPSIS (TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION) - M Panji Ismail (JURNAL INFORMATIKA DAN KOMPUTER, 2018)
The scholarship path is one of the paths used by the University of Technology Yogyakarta (UTY) in accepting new students. The track consists of seven criteria: school accreditation, family condition, report card score, achievement, written test, interview test. In order to process the criteria, it is necessary to have a Decision Support System (DSS) capable of conducting the scholarship selection process quickly, accurately and objectively. DSS is a system that can perform a decision-making process based on the human mindset. SPK can tolerate any kind of data whether it is certain or uncertain. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is a Multi-Criteria Decision Making (MCDM) category which is a decision-making technique of some alternative options, especially Multi Attribute Decision Making (MADC). TOPSIS aims to determine the ideal ideal solution and the ideal negative solution of the scholarship criteria. A positive ideal solution maximizes benefit criteria and minimizes cost criteria, whereas a negative ideal solution maximizes cost criteria and minimizes benefit criteria. The research methodology used is SDLC (System Development Life Cycle) and system implementation built using Delphi 7 programming language and data processing using DBMS SQL Server 2012.. The results of the system show that the system provides accurate and valid results in accordance with the data owned by prospective students so that full scholarship can be given in the right target.